Pengaruh Effective Monitoring, Green Competitive Advantage, dan Personal Financial Need terhadap Financial Shenanigans pada Perusahaan Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia - Dewi, Annisa Nathania; Budiwitjaksono, Gideon Setyo; Azmiyanti, Rizdina (Jurnal Akuntansi Terapan dan Bisnis, 2025)
The growth of Indonesia’s technology sector has become a significant driver of national economic development. However, this growth has also been accompanied by an increased risk of financial shenanigans or financial statement manipulation. This condition highlights the importance of understanding the factors that influence the potential for fraud, particularly in developing technology companies. The research employs a quantitative approach using secondary data. The results show that effective monitoring and personal financial need have a positive and significant effect on financial shenanigans, while green competitive advantage has a negative effect. These findings imply that the presence of independent commissioners does not necessarily prevent financial shenanigans if the supervisory function is not carried out substantively. In addition, personal financial pressure may increase the likelihood of opportunistic managerial behavior, whereas a strong commitment to green competitive advantage can serve as both an ethical and strategic mechanism to reduce the tendency of financial shenanigans in technology companies.